Analysis And Implementation Of Wireless Lan Authentification Using Php And Mysql Api At Adeeva Hotel - Revaldi Mirza Pratama; Indra Kanedi; Ahmad Fikri Sallaby (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Hotel Adeeva is one of the hotels in Bengkulu City that provides various services, such as room rental, meeting money rental, party money rental, restaurant and others. The computer network at Hotel Adeeva Bengkulu City is currently connected to the internet network, the utilization of the LAN network, especially the internet at Hotel Adeeva Bengkulu City is not optimal, because it is still used for staff and employees, while guests cannot enjoy it. This study aims to implement wireless LAN authentication using the PHP API at Hotel Adeeva Bengkulu City. The study uses a quantitative experimental method. With the existence of a wireless LAN authentication system using the PHP API, it is hoped that the LAN network, especially the internet, can be enjoyed by all (staff, employees and guests). So that it adds value to the services at Hotel Adeeva. The Wireless LAN authentication system based on the PHP API uses the Mikhmon application, so that it can manage users in terms of bandwidth, users and active duration